1999
DOI: 10.1007/s001340050984
|View full text |Cite
|
Sign up to set email alerts
|

Current definitions of acute lung injury and the acute respiratory distress syndrome do not reflect their true severity and outcome

Abstract: Since the use of PEEP in the American-European Consensus criteria for ARDS is not mandatory, that definition does not reflect the true severity of lung damage and outcome. Our data support the need for guidelines based on a specific method of evaluating oxygenation status before the American-European Consensus definition is adopted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
94
3
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(112 citation statements)
references
References 20 publications
9
94
3
6
Order By: Relevance
“…1 Recent data suggest that there may be distinct subgroups of ALI/ARDS patients with markedly different responses to higher PEEP. [38][39][40][41][42] Whole-body computed tomography has demonstrated that higher PEEP in patients with a low percentage of recruitable lung (non-responders) provides little benefit and may be harmful. 39 In another study, nonresponders (Ͻ 150 mL alveolar recruitment) who received a higher PEEP protocol similar to that used in one of the studies in our systematic review 15 experienced no change in arterial oxygenation, but did experience significant increases in static lung elastance.…”
Section: Discussionmentioning
confidence: 99%
“…1 Recent data suggest that there may be distinct subgroups of ALI/ARDS patients with markedly different responses to higher PEEP. [38][39][40][41][42] Whole-body computed tomography has demonstrated that higher PEEP in patients with a low percentage of recruitable lung (non-responders) provides little benefit and may be harmful. 39 In another study, nonresponders (Ͻ 150 mL alveolar recruitment) who received a higher PEEP protocol similar to that used in one of the studies in our systematic review 15 experienced no change in arterial oxygenation, but did experience significant increases in static lung elastance.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most frequently studied indices is the Pa,O 2 / FI,O 2 , although contradictory results concerning its ability to predict outcome have been reported in adult AHRF/ARDS [2,[27][28][29][30][31][32][33][34][35]. Some authors have argued that the ratio may not be predictive at inclusion, but after 24 or 48 h [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have argued that the ratio may not be predictive at inclusion, but after 24 or 48 h [30,31]. Two paediatric studies on children with generalised AHRF also failed to clearly define respiratory parameters for outcome prediction [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…From a therapeutic point of view, we need a rigorous stratification of lung injury severity since the intensity and modality of ventilatory support and adjunctive therapies should differ depending on the degree of hypoxemia. From the research perspective, a precise definition helps to standardize studies on etiology, pathophysiology and treatment [6], improves our ability to compare data among studies and centers, and helps in evaluating the natural history, incidence, and prognosis of ARDS [7].…”
Section: Searching For a Satisfactory Ards Definitionmentioning
confidence: 99%
“…This definition was challenged by Villar et al [7,9,10], when they demonstrated that the PaO 2 response to standardized ventilatory settings (which included a specific level of PEEP and FiO 2 ) allowed the separation of ARDS patients into several groups with different severity and outcome. They observed that: (1) about half of the patients were improperly classified, and (2) ARDS patients could be uniformly stratified according to their response to a PEEP-FiO 2 trial.…”
Section: Searching For a Satisfactory Ards Definitionmentioning
confidence: 99%